Le livre français d'Istanbul (1730-1908) - Johann Strauss (Revue des Mondes Musulmans et de la Méditerranée)
The present paper intends to shed light on books published in French in the capital of the Ottoman Empire. Publication of books in French started in 1730 with J.-B. Holderman's Grammaire turque printed by Ibrahim Muteferrika. Promising developments at die end of the century were followed by a period of stagnation. The number of books in French increased considerably in die second half of die nineteenth century in the aftermath of the Crimean War. They include, apart from official publications, mainly works on legislation, language, history and medecine. Purely literary works (novels, poetry) are scarce. Among the authors we find dragomans, missionaries, school teachers, journalists, government officials, and members of the minorities as well as native Turks. It is true that most of these books have not stood the test of time. But a few of them, such as Moustapha Djelaleddin's Les Turcs anciens et modernes (1869), have had an enormous impact which lasted up to the Republican period.